Nutritional values and antioxidant activity of noodles incorporated with black face general (strobilanthes crispus) - Set, Shu Hui (2022)
Strobilanthes crispus, known as Black Face General is one of the herbal plants readily found in Malaysia. It has been used in some traditional remedies due to its antioxidant potential and pharmaceutical properties. In this study, the noodle was made by incorporating different concentrations of fresh S. crispus leaves (3, 5, and 10%) to determine the nutritional values, antioxidant activities (TPC, DPPH, and FRAP), and physicochemical properties (texture and color). Analysis of variance (ANOVA) and Tukey test were carried out to examine the significant difference of results at p= 0.05 level. Based on the result, proximate analysis revealed that there was a significant difference (p<0.05) in the amount of moisture, ash, protein, fat, and fiber across samples except carbohydrates content (p>0.05). In all antioxidant assays, 10% S. crispus noodles showed the highest antioxidant capacity with significant difference between samples (p<0.05): TPC (1.75 ± 0.11 mg GAE/mL), DPPH (IC50 = 1958.4 ± 194.58 μM/mL) in references to ascorbic acid (IC50 = 27.64 ± 0.74 μM/mL), and FRAP (141.44 ± 8.22 μM Fe(Ⅱ)/mL). The antioxidant activity of 0% control noodles were 1.38 ± 0.15 mg GAE/mL, IC50 = 2676.34 ± 362.95 μM/mL, and 60.03 ± 6.4 μM Fe(Ⅱ)/mL for TPC, DPPH, and FRAP respectively. There was a significant decrease in hardness along the S. crispus concentration where the 10% S. crispus noodles had the lowest value (42.66 ± 0.89 N). Besides, the tensile strength difference among samples was not significant (p>0.05). As the concentration of S. crispus increases, L* and a* values decreased, b* values increased, this indicated that the noodle became darker and stronger in a green and yellow hue due to the presence of chlorophyll pigment. Overall, 10% S. crispus noodles effectively enhance antioxidant activity compared to 3% S. crispus and control noodles.